Test of ovarian cancer multiplex xMAP technology panel - Windrichová, Jindra; Pražáková, Markéta; Novotný, Zdeněk; Topolčan, Ondřej; Čásová, Miroslava; Holubec, Luboš (Anticancer research, 2009)
BACKGROUND: An ovarian cancer marker panel including leptin, prolactin, osteopontin, insulin-like growth factor II (IGFII), macrophage migration inhibitory factor and CA125 was tested for multiplex marker measurement. Multiplex was compared to single assayed tumour markers: CA125, TPS, thymidine kinase, monototal and HE4.
Keywords: financování organizované; dospělí; nádory vaječníků; CA-125 Antigen; Female; Thymidine Kinase; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; epididymální sekreční proteiny; Ovarian Neoplasms; Aged, 80 and over; thymidinkináza; Protein Array Analysis; Financing, Organized; peptidy; Epididymal Secretory Proteins; nádorové biomarkery; Aged; antigen CA-125; Young Adult; čipová analýza proteinů; Peptides; Biomarkers, Tumor; lidé středního věku; senioři nad 80 let; senioři; Middle Aged; mladiství; Humans